A Biomechanical Analysis of Shoulder Muscle Excursions During Abduction, After the Treatment of Massive Irreparable Rotator Cuff Tears Using Superior Capsular Reconstruction (SCR), Bursal Acromial Reconstruction (BAR), and SCR with BAR. (June 2022) - Labib, Michael; Amirouche, Farid; Pradhan, Sonia; Bobko, Aimee; Koh, Jason
Introduction: Current understanding of the biomechanical effects of treatment options for irreparable rotator cuff (RC) tears is lacking. This study examines how shoulder muscle lengths and excursions are affected by superior capsular reconstruction (SCR), bursal acromial reconstruction (BAR), and SCR with BAR, following a complete supraspinatus tear. Method: Six fresh-frozen cadaveric shoulders were examined. Deltoid and RC muscle lengths were measured at 0, 30, 45, 60, and 90° of shoulder abduction under six conditions: (1) intact, (2) partially torn supraspinatus, (3) completely torn supraspinatus, (4) SCR, (5) SCR with BAR, and (6) BAR. Muscle excursions from 0–90° of abduction were then calculated. Results: Subscapularis muscle lengths after SCR, BAR, and SCR with BAR were significantly greater (post-hoc Tukey HSD test; p  < .01) compared to the other conditions. Supraspinatus, infraspinatus, teres minor, and deltoid lengths were not significantly different (ANOVA test; p  > .01) between the conditions. All muscle excursions remained statistically similar between the conditions (ANOVA test; p  > .01). Conclusion: These findings demonstrate that the use of SCR, BAR, or SCR with BAR for a complete supraspinatus tear, may increase subscapularis muscle length while maintaining other shoulder muscle lengths. An increase in subscapularis length can allow for more effective subscapularis muscle strengthening and increased compensatory function in the long term. Additionally, all shoulder muscle excursions are preserved after partial or complete supraspinatus tears and after SCR, BAR, or SCR with BAR. Therefore, these surgical treatments can initially normalize shoulder muscle function during 0–90° of abduction, after an irreparable supraspinatus tear.